EXPLORATION OF ADOPTION OF HEALTH LIFESTYLE FOR SECONDARY PREVENTION OF NON COMMUNICABLE DISEASES (STROKE, DIABETES AND HYPERTENSION) AMONG CLIENTS AT MZUZU CENTRAL HOSPITAL MALAWI, 2013 - Mbakaya Chingatichifwe, Balwani; Dodge, Ed.; Chideme-Munodawafa, Auxillia; Masulani Mwale, Charles; Bvumbwe, Thokozani (European Scientific Journal, ESJ, 2014)
Background: Noncommunicable diseases (NCDs) kill more than 36million people each year. Nearly 80% of NCD death (29 million) occurs inlow and middle income countries (WHO, 2010). In Malawi, NCDs accountfor at least 12% of total Disability Adjusted Life Years (WHO 2010) .Objective: The main objective was to explore adoption of healthy lifestylefor secondary prevention of stroke, diabetes and hypertension among clientsreceiving treatment at Mzuzu Central Hospital. Methods: A cross sectionalanalytical study design was used. Sixty three participants aged 18 years andabove were selected using a purposive sampling technique, who had all, ortwo or one of the following NCDs; stroke, diabetes or hypertension, andreceiving treatment at Mzuzu Central Hospital participated in the study. Aninterviewer administered questionnaires was used to collect data. Findings:The majority were females (74.6%; 47/63), and the median age of theparticipants was 60 years (Q1=51; Q3=65). Although most participantsfailed to define stroke, diabetes and hypertension (88.9%), failed to mentionthe recommended healthy lifestyle (65.1%) as regards its prevention and alsofailed to mention complications of NCDs (85.7%), the majority (85.7%)indicated to have received health education on NCDs. Furthermore, thefindings revealed that 71.4% did not perceive to be at risk of developingcomplications from their diagnosed condition despite the given healtheducation. Participant consumed fewer servings of fruits and vegetables per day, and did not practice healthy lifestyle in general. Conclusion: Healtheducation need to comprehensively cover interventions for prevention ofNCDs. Besides that, reinforcement of acquired knowledge on NCDs amongclient should be emphasized so as to increase the chances to adopt andpractice healthy lifestyle.